Benefits of Interactive Whiteboards for Teachers and Students - Pazilova Nasibaxon Muhammadqosimovna; Usmonova Dona Satvoldiyevna (Zien Journals, 2022)
This article is deals with the problems of teaching and the importance of interactive whiteboards. This article mainly focuses on using interactive whiteboards, materials of the lesson, the role of teachers and students in classroom.
Keywords: interactive whiteboards; classroom; materials; interactive